A PdCu nanoalloy catalyst for preferential CO oxidation in the presence of hydrogen. (17th February 2021) - Khobragade, Rohini; Dahake, Pranali; Labhsetwar, Nitin; Saravanan, Govindachetty
Abstract : Alloy PdCu nanoparticles for CO oxidation in the presence and absence of hydrogen. Abstract : Catalytic oxidation of carbon monoxide (CO) is one of the essential steps for several environment- and energy-related applications. Here, we report the synthesis of alloy PdCu nanoparticles supported on an Al2 O3 support as a catalyst for effective removal of CO from H2 -rich flue gases. The alloy phase between Pd and Cu was formed by deposition of organometallic Pd- and Cu-precursors on the Al2 O3 support followed by thermal reduction under H2 . The alloy PdCu nanoparticles (average size: 30 nm) are in a spherical shape and they are distributed in the range between 10 and 80 nm. The alloy PdCu catalyst showed improved CO oxidation performance both in the presence and absence of H2 compared to that of the reference Pd catalyst. It is also inferred that the alloy PdCu catalyst showed an onset temperature ( T o ) of 50 °C in the presence of H2 compared to that of CO oxidation in the absence of H2 ( T o = 100 °C). In addition, the alloy PdCu catalyst showed selective CO oxidation performance below a temperature range of 300 °C. Therefore, the formation of the Pd-based alloy structures may have potential as the preferential CO oxidation catalyst for the catalytic removal of CO from various flue gases.